2021
DOI: 10.1007/s11240-021-02116-0
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-vitrification methods for apical bud cryopreservation of yacon [Smallanthus sonchifolius (Poepp. and Endl.) H. Rob.]

Abstract: This study aimed to develop a cryopreservation protocol for the long-term preservation of yacon [Smallanthus sonchifolius (Poepp. and Endl.)], an Andean crop with high fructooligosaccharide content in its tuberous roots. Initially, the cryopreservation protocol was developed using a yacon clone originated from Ecuador classi ed as ECU 41. Osmotic dehydration of apical buds (2-3 mm long) was carried out by assessing two plant vitri cation solutions, PVS2 (15, 30, and 60 min) at 0°C and PVS3 (30, 45, 60, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…H.Rob.] [149]. Dr-vi is currently the most widely applied cryoprotocol for cryopreserving plant germplasm within genebanks, including those for potato [66,69,150,151], cassava [69], sweet potato [151] and yam [70].…”
Section: Droplet-vitrification Methods (Dr-vi)mentioning
confidence: 99%
See 2 more Smart Citations
“…H.Rob.] [149]. Dr-vi is currently the most widely applied cryoprotocol for cryopreserving plant germplasm within genebanks, including those for potato [66,69,150,151], cassava [69], sweet potato [151] and yam [70].…”
Section: Droplet-vitrification Methods (Dr-vi)mentioning
confidence: 99%
“…They found that PVS2 or PVS4 incubations at 23 • C for 15-30 min achieved satisfactory shoot regrowth, while PVS3 was impractical for Dr-vi due to its weak adhesion to the aluminum foil [117]. In contrast, the PVS3 dehydration was later optimized and applied successfully in Dr-vi for shoot tip cryopreservation of potato [131], yacon [149], and ulluco [155]. Additionally, PVS3 has been routinely applied for cryopreserving potato shoot tips at the gene bank of Gatersleben, Germany [131].…”
Section: Dehydration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The droplet-vitrification method is derived from the DMSO droplet methods proposed by Kartha et al [146], and Kaczmarczyk et al [149] and Schaefer-Menhur et al [150]. The procedure is similar to the droplet method but with highly concentrated cryoprotective solution PVS2 [104,147,[150][151][152] or PVS3 either in original or in its modification PVS3-M4 [122] or both PVS2 and PVS3 [97,113,126] before ultra-fast cooling. Rewarming of the samples is usually done in unloading solution temperated in a 40 • C sterile water bath for 1-2 min.…”
Section: Vitrification Solution and Cryopreservation Methodsmentioning
confidence: 99%
“…Therefore, there is no generic time for PVS2. For example, in apple the droplet-vitrification method had the highest regrowth percentage after 30-50 min PVS2 exposure at room temperature [109]; in potato droplet-vitrification had the highest regrowth percentage after 50 min PVS2 exposure at 0 • C [110]; in shallot droplet-vitrification had the highest regrowth percentage after 40-60 min PVS2 exposure at 0 • C [111]; in grapevine droplet-vitrification had the highest regrowth percentage after 90 min PVS2 exposure at 0 • C [112], and in yacon droplet-vitrification had the highest regrowth percentage after 60 min PVS2 exposure at 0 • C [22,113]. DMSO and Gly penetrate the cell wall membrane and increase cellular osmolality avoiding ice formation [7,38,114].…”
Section: Vitrification Solutions and Modificationsmentioning
confidence: 99%